Swyer-James-Macleod syndrome as a rare cause of unilateral hyperlucent lung: Three case reports. Issue 6 (February 2019) - Machado, Daniela; Lima, Filipa; Marques, Catarina; Monteiro, Regina
Abstract: Rationale: Swyer-James-Macleod syndrome (SJMS) is a rare lung disorder characterized by unilateral hyperlucent lungs which arises as a complication of bronchiolitis obliterans. It is typically diagnosed during childhood, although some patients may only be diagnosed in adulthood, often as an incidental finding, but others due to recurrent chest infections. Patient concerns: Three patients were referred to our institution with complaints of dyspnea on exertion, chronic productive cough, and recurrent pulmonary infections. Two of them had a history of lower respiratory tract infections during childhood. Diagnosis: A computed tomography scan was performed and showed unilateral reduced density of the lung and bronchiectasis in the 3 patients. Based on the clinical presentation and radiologic features, the diagnosis of SJMS was established. Interventions: Patients started inhaled corticosteroids and long acting beta agonist, vaccines to prevent respiratory infections were administered and airway clearance techniques were taught. Outcomes: Two patients became asymptomatic with inhaled therapy and no recurrent chest infections were observed over a 3-year follow-up period, being discharged from our institution to the general practitioner. The 3rd patient had some improvement in the frequency of pulmonary infections and dyspnea, without improvement in respiratory function tests, maintaining vigilance at our center. Lessons: These cases highlight the importance of being aware of this condition and its frequent association with bronchiectasis, which may adversely affect the prognosis, to manage patients appropriately and prevent recurrent pulmonary infections.